2014
DOI: 10.1111/jgs.12744
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Observed In‐Home Behaviors and Self‐Reported Low Mood in Community‐Dwelling Older Adults

Abstract: Objective Using novel monitoring technologies, we sought to ascertain the association between self-report of low mood and unobtrusively measured behaviors (walking speed, time out of residence, frequency of room transitions, and computer use) in community-dwelling older adults. Design Longitudinal cohort study of older adults whose homes were outfitted with activity sensors. The participants completed internet-based weekly health questionnaires with questions about mood. Setting Apartments and homes of old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Time out of home has also been shown to relate to relevant behavioral and psychological changes that may be commonly experienced by MCI or dementia patients such as low mood. Thus, using 18,960 weekly observations of online reported mood ratings over a period of 120 weeks, it was found that during weeks of low mood, participants spent less time out of residence, but did not show changes in walking speed or movement about their home measured by room transitions (Thielke et al, 2014 ).…”
Section: Research Evidencementioning
confidence: 99%
“…Time out of home has also been shown to relate to relevant behavioral and psychological changes that may be commonly experienced by MCI or dementia patients such as low mood. Thus, using 18,960 weekly observations of online reported mood ratings over a period of 120 weeks, it was found that during weeks of low mood, participants spent less time out of residence, but did not show changes in walking speed or movement about their home measured by room transitions (Thielke et al, 2014 ).…”
Section: Research Evidencementioning
confidence: 99%
“…Similarly, subtle changes in medication use (Hayes, Larimer, Adami, & Kaye, 2009), walking speed (Dodge, Mattek, Austin, Hayes, & Kaye, 2012; Silbert, 2012), sleep patterns (Dodge et al, 2012), and overall activity level (Kaye et al, 2011) have been identified by in-home monitoring technologies as potential early signs of incipient cognitive decline. In a related finding, Thielke et al report associations between monitored in-home behaviors and self-reported low mood (Thielke et al, 2014). …”
Section: Discussionmentioning
confidence: 93%
“…For example, a comprehensive psychometric battery and behavioral assessment is completed with the intention of determining a change in cognitive status that also meets current standards of clinical diagnosis. The self-report and clinical outcome measures are a critical component for enabling ORCATECH to make connections between sensed behaviors and true health outcomes (Thielke et al, 2014).…”
Section: Self-assessment and Annual Screeningsmentioning
confidence: 99%